Adaptive PID control using TSK elliptic fuzzy and static feedforward for observable disturbance rejection in industrial heating ovens - Ali Rospawan; Clara Lavita Angelina; I Made Andik Setiawan; Zanu Saputra; Ocsirendi Ocsirendi; Aan Febriansyah; Indra Dwisaputra; Dedy Ramdhani Harahap (Journal of Mechatronics, Electrical Power, and Vehicular Technology, 2026)
This paper presents an advanced control strategy aimed at accelerating the temperature recovery time in industrial heating ovens, particularly in response to observable disturbances such as periodic door openings. The proposed method combines a Takagi-Sugeno-Kang (TSK) elliptic fuzzy-based adaptive proportional-integral-derivative (PID) control with a static feedforward (FF) control strategy. The TSK elliptic fuzzy system models the input-output dynamics and adaptively adjusts the PID gains, allowing the controller to respond effectively to varying system conditions. The static feedforward control is designed to specifically counteract the measurable disturbances to shorten recovery time and improve stability. The strategy is validated through both simulation and experiment on a low-cost STM32 microcontroller. Compared with a conventional PID controller, it reduced the RMSE by 32.27 % and the ISE by 54.13 %, together with a recovery time shortened by approximately 72 s, reflecting the faster disturbance recovery achieved by the static feedforward action. Experimental results confirmed these findings, with a higher feedforward gain further reducing the temperature drop and accelerating recovery. The proposed technique offers a reliable and practical solution for practitioners in managing similar disturbance patterns in industrial settings.